2020
DOI: 10.1136/flgastro-2019-101353
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the development of psychological morbidity in inflammatory bowel disease: a systematic review

Abstract: BackgroundPsychological morbidity in inflammatory bowel disease is common with significant impact on quality of life and health outcomes, but factors which predict the development of psychological morbidity are unclear.AimTo undertake a systematic literature review of the predictors of psychological morbidity in patients with inflammatory bowel disease.MethodsElectronic searches for English-language articles were performed with keywords relating to psychological morbidity according to the Diagnostic and Statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…Studies examining gut-to-brain effects remain limited and our results are similar to those already observed. [10] However, all of the brain-to-gut studies we identified only included individuals without pre-existing common mental disorders at baseline, which strengthens our findings as it means there is unlikely to be confounding.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Studies examining gut-to-brain effects remain limited and our results are similar to those already observed. [10] However, all of the brain-to-gut studies we identified only included individuals without pre-existing common mental disorders at baseline, which strengthens our findings as it means there is unlikely to be confounding.…”
Section: Discussionsupporting
confidence: 72%
“…In this study, although there was a trend towards depression influencing the course of CD, the results were not significant. [9] In a systematic review examining gut-to-brain effects there was a statistically significant association between aggressive disease and subsequent development of depression in patients with IBD, [10] but only in a single study. [11] However, to date, there has been no definitive systematic assessment of gut-to-brain and brain-to-gut effects in patients with IBD.…”
Section: Introductionmentioning
confidence: 99%
“…It was mentioned in the introduction that depression or other psychiatric disorders may precede the onset of inflammatory bowel disease, RA or diabetes [ 22 24 , 26 , 27 , 29 , 34 38 ]. It may also develop after the onset of all these conditions [ 20 , 22 , 24 27 , 30 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…IBD is associated with compromised life quality, extensive morbidity, and even hospitalization, depending on the stage and severity of the disease . Psychologically, IBD could lead to morbidity with prevalence rates over 50%, which is frequently accompanied by sick leave, reduced productivity, and even unemployment . However, the pathogenesis of IBD remains largely unknown, and multiple factors, such as host immunity, enteric microorganisms, and environmental factors, collectively lead to homeostasis dysregulation and inflammatory outcome in the GIT. , It is generally acknowledged that increased reactive oxygen species (ROS), which originate from gastrointestinal mucosa and infiltrated immune cells, lead to a pathological inflammatory response. , The outcome of ROS overproduction could be severe, ranging from blunted or absent microvilli to colitis-associated colon carcinoma disease. Clinical and experimental studies have proven that ROS production largely exacerbates the process of IBD and is regarded as a potential therapeutic target for IBD treatment. , Interestingly, the benefit of the standard care therapy such as anti-inflammatory drugs (mesalazine) and probiotics is associated with an antioxidant mechanism in mouse models. However, these existing therapies are far from perfect in terms of potency and durability of ROS modulation in the context of IBD.…”
Section: Introductionmentioning
confidence: 99%
“…1 Psychologically, IBD could lead to morbidity with prevalence rates over 50%, which is frequently accompanied by sick leave, reduced productivity, and even unemployment. 2 However, the pathogenesis of IBD remains largely unknown, and multiple factors, such as host immunity, enteric microorganisms, and environmental factors, collectively lead to homeostasis dysregulation and inflammatory outcome in the GIT. 3,4 It is generally acknowledged that increased reactive oxygen species (ROS), which originate from gastrointestinal mucosa and infiltrated immune cells, lead to a pathological inflammatory response.…”
Section: Introductionmentioning
confidence: 99%